Wendel and the robots - Riddell, Chris (Macmillan Children's Books, 2015)
If his inventions go wrong, Wendel just throws them away and starts again. So when Clunk, his robot assistant, fills the sock drawer with cups and saucers and makes tea in a boot, Wendel throws him on the scrapheap and makes himself a new assistant: the Wendelbot. But he gets more than he bargained for, and soon Wendel finds himself on the scrapheap. Can he win back his workshop from the mighty Wendelbot?